Adoption Levels of Cocoa Rehabilitation Programmes in South-west Nigeria - Akinnagbe Oluwole Matthew (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Cocoa is an important crop to the economies of countries such as Nigeria, Cote D’Ivoire, Ghana and Cameroon in West Africa. In an effort to revive cocoasector and increase cocoa production in Nigeria led to cocoa rehabilitation programme (CRPs) by the Federal Government of Nigeria. This study ascertainedthe adoption levels of farmers in cocoa rehabilitation programmes in South-west Nigeria. Data for the study were collected from 240 cocoa farmers through theuse of interview schedule and focus group discussion. Multistage sampling procedure was used in selecting respondents. Data were analysed using percentageand mean statistics. Results revealed that, adoption level was low for coppicing techniques (38.0%, 32.0% and 33.0%) and complete replanting (25.0%, 27.0% and26.0%) of cocoa rehabilitation programme, respectively, for the three groups of farmers (farmers that benefitted from government agency cocoa resuscitationprogramme, farmers that benefitted from non-governmental agency cocoa resuscitation programme and farmers that benefitted from both governmental and nongovernmental agencies). Planting of young cocoa seedling under old cocoa trees (98%, 94%, 95%) and selective planting/gapping up (68.0%, 81.0% and 79.0%) had a very high adoption level for the three groups of the farmers. The most helpful agency in the adoption of cocoa resuscitation programmes was Agricultural Development Programme. To improve the level of adoption of cocoa resuscitation programmes, the federal government of Nigeria should further intensifyefforts in encouraging more farmers in cocoa rehabilitation programme by providing the necessary incentives (like distribution of free cocoa seedlings) to the farmers as at when necessary.